Ethopharmacological analysis of the open elevated plus-maze in mice - Sorregotti, Tatiani [UNESP]; Mendes-Gomes, Joyce [UNESP]; Rico, Javier Leonardo [UNESP]; Rodgers, Robert John; Nunes-de-Souza, Ricardo Luiz [UNESP] (Elsevier, 2013)
Exposure of rodents to an open elevated plus-maze (oEPM) elicits antinociception and increases plasma corticosterone levels. However, no studies have yet assessed the defensive behaviour repertoire of animals in this modified test. In Experiment 1, factor analysis was employed to characterise the behavioural profile of mice exposed to the oEPM. Experiments 2 and 3 assessed the effects of acute alprazolam (0.5-1.5. mg/kg; diazepam 0.5-1.5. mg/kg), pentylenetetrazole (10.0-30.0. mg/kg), yohimbine (2.0-6.0. mg/kg), mCPP (0.3-3.0. mg/kg), and acute and chronic fluoxetine (10.0-30.0. mg/kg) and imipramine (1.0-15.0. mg/kg) on behaviours identified in Experiment 1. The factor analyses revealed that behaviour in the oEPM can largely (77% total variance) be accounted for in terms of 3 factors: factor 1 ('. depth exploration'; e.g. head-dipping on the arms), factor 2 ('. cautious exploration of arms'; e.g. flatback approach), and factor 3 ('. risk assessment'; stretched attend postures - SAP). Experiments 2 and 3 showed that, over the dose range used, alprazolam selectively attenuated all measures of defensiveness. Similar, though more modest, effects were seen with diazepam. Confirming the intensity of the emotional response to the oEPM (nociceptive, endocrine and behavioural), relatively few significant behavioural changes were seen in response to the anxiogenic compounds tested. Although acute fluoxetine or imipramine treatment failed to modify behaviour in the oEPM, chronic fluoxetine (but not chronic imipramine) attenuated total flat back approach and increased head dipping outside the central square. Together, the results indicate that the oEPM induces behavioural defensive responses that are sensitive to alprazolam and chronic fluoxetine. © 2013 Elsevier B.V.
Keywords: Antidepressants; Anxiolytics and anxiogenics; Defensive behaviour; Factor analysis; Mice; Open elevated plus-maze; (3 chlorophenyl)piperazine; alprazolam; diazepam; fluoxetine; imipramine; pentetrazole; yohimbine; animal behavior; animal experiment; arm movement; behavior change; body posture; chronic drug administration; controlled study; defensive behavior; drug sensitivity; emotion; endocrine function; ethnopharmacology; exploratory behavior; head movement; male; maze test; mouse; nociception; nonhuman; open elevated plus maze; priority journal; risk assessment